Combating oil spill problem using plastic waste. (October 2015) - Saleem, Junaid; Ning, Chao; Barford, John; McKay, Gordon
Highlights: Up-cycling one type of pollution i.e. plastic waste and successfully using it to combat the other type of pollution i.e. oil spill. Synthesized oil sorbent that has extremely high oil uptake of 90 g/g after prolonged dripping of 1 h. Synthesized porous oil sorbent film which not only facilitates in oil sorption but also increases the affinity between sorbent and oil by means of adhesion. Abstract: Thermoplastic polymers (such as polypropylene, polyethylene, polyethylene terephthalate (PET) and high density polyethylene (HDPE)) constitute 5–15% of municipal solid waste produced across the world. A huge quantity of plastic waste is disposed of each year and is mostly either discarded in landfills or incinerated. On the other hand, the usage of synthetic polymers as oil sorbents, in particular, polyolefins, including polypropylene (PP), and polyethylene (PE) are the most commonly used oil sorbent materials mainly due to their low cost. However, they possess relatively low oil absorption capacities. In this work, we provide an innovative way to produce a value-added product such as oil-sorbent film with high practical oil uptake values in terms of g/g from waste HDPE bottles for rapid oil spill remedy.